Evaluation and Planning of Strong and Durable Roads Due to Overloaded Vehicle (Case Study : The National Road Bts. Kab. Konawe Utara/Kab. Konawe – Pohara) - Kurniawan, Reza; Mochtar, Indrasurya Budisatria; Siagian, Freddy (Journal of Infrastructure & Facility Asset Management, 2023)
In 2020, more than half of the national road length of Bts. Kab. Konawe Utara/Kab. Konawe – Pohara is in a heavily damaged condition. This is due to the heavy vehicles used for the development of the Konawe Industrial Estate passing through this road. This research was carried out by collecting primary data from vehicle tire pressure surveys and secondary data in the form of the results of the 2021 vehicle weight test. Axle loads in the field can be predicted using vehicle tire pressure. Vehicle Damage Factor (VDF) calculation is carried out and compared with the VDF given by the 2017 Revision Pavement Design Manual (MDP). From the various VDF data, a Cumulative Equivalent Single Axle Load (CESAL) calculation is also carried out and also compared. The results obtained from this study are that the actual VDF at the study site for vehicle classes 6b and 7a are respectively greater up to 1.58 and 7.37 times than the actual VDF for the Sulawesi region given by MDP 2017. In direct proportion to that, CESAL due to field loads is greater is up to 3.03 times greater than CESAL due to the actual load for the Sulawesi region provided by the 2017 MDP. The CESAL value due to field loads is up to 7.25 times greater than the CESAL due to the normal load provided by the 2017 MDP.